Mekanisme Ideal Penyelesaian Clerical Error dalam Peraturan Perundang-Undangan di Indonesia (Perbandingan terhadap Inggris, Amerika Serikat, dan Singapura) - Eka N.A.M. Sihombing; Cynthia Hadita (Jurnal Penelitian Hukum De Jure, 2023)
The problem of article clerical error creates multi-interpretation, ambiguity, and obscure in understanding the meaning of the substance of the Article so a mechanism is needed to optimize the authority of the Constitutional Court. This study aims to optimize the Constitutional Court's role in providing a legal interpretation of clerical error. The research method used is normative juridical with a doctrinal approach. The results showed that clerical error resulted in multiple interpretations of the substance of an Article. Thus, a legal interpretation by the Constitutional Court for the clerical error is needed which needs to be optimized for its role as a preventive multi-interpretation of the substance of articles in laws and regulations in Indonesia. For example, there is a newly passed law, so to change an article that is not by the system of changing/revising the law for a long time, so to shorten the mechanism for change/revision it requires legal interpretation in the Constitutional Court.